Negative plate and preparation method thereof, battery and electric equipment

By setting an active substance coating with particle size gradient on the negative electrode sheet of the battery and using high and low swelling binder, the problem that existing negative electrode sheets of the battery are difficult to take into account both power and life, improving the energy density and rate performance of the battery, and extending the service life.

CN119764324APending Publication Date: 2025-04-04BYD CO LTD

Patent Information

Application Number
CN202411707148.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The active substance of the existing battery negative electrode sheet has a single particle size, making it difficult to take into account both power performance and service life. The large particle size can easily affect the rate performance and lead to short circuit problems.

Method used

The first coating and the second coating are arranged sequentially outside the current collector. The particle size of the active substance D50 of the first coating is 5 μm to 12 μm, and the particle size of the active substance D50 of the second coating is 1 μm to 7 μm. By adjusting the particle size and using a high and low swelling binder, the charging and discharge performance and service life of the battery are optimized.

Benefits of technology

It improves the compaction density and battery energy density of the negative electrode sheet, enhances the battery level charge and discharge rate performance, reduces the risk of short circuit, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764324A_ABST
    Figure CN119764324A_ABST
Patent Text Reader

Abstract

The invention discloses a negative plate and a preparation method thereof, a battery and electric equipment. The negative plate comprises a current collector, a first coating and a second coating. Wherein the first coating and the second coating comprise active substances, the D50 particle size of the active substance of the first coating is greater than the D50 particle size of the active substance of the second coating, the D50 particle size of the active substance of the first coating is 5-12 [mu] m, and the D50 particle size of the active substance of the second coating is 1-7 [mu] m. According to the negative plate provided by the invention, the compaction density of the negative plate is improved, the energy density of the battery is improved, contact sites between active substances and between the active substances and the current collector are increased, and the hierarchical charge-discharge rate performance of the battery is improved. And meanwhile, the second coating is arranged on one side of the contact diaphragm, so that the short circuit condition caused by the morphology hardness of an active substance of the second coating can be effectively reduced, the process yield is improved, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet and a preparation method thereof, a battery and an electrical device. Background Art

[0002] In the related art, the dressing layer used for coating the negative electrode of the battery includes an active material. However, the particle size of the active material in the currently commonly used dressing layer is single, making it difficult for the negative electrode to take into account both power performance and service life. At the same time, the particle size of the active material in the dressing layer is large, which is easy to affect the battery rate performance. At the same time, the active material is irregular and sharp in shape, which is easy to pierce the diaphragm during the manufacturing process, causing battery short circuit problems. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the first purpose of the present invention is to provide a negative electrode sheet that is conducive to improving the compaction density of the negative electrode sheet, improving the battery energy density, and improving the battery-level charge and discharge rate performance. Improve the process yield and extend the service life of the battery.

[0004] The second object of the present invention is to provide a method for preparing a negative electrode sheet.

[0005] The third object of the present invention is to provide a battery.

[0006] A fourth object of the present invention is to provide an electrical device.

[0007] According to the first aspect of the present invention, the negative electrode sheet includes: a current collector; a first coating, the first coating is arranged on the surface of the current collector; and a second coating is arranged on a side of the first coating away from the current collector, wherein the first coating and the second coating include an active substance, the D50 particle size of the active substance of the first coating is larger than the D50 particle size of the active substance of the second coating, the D50 particle size of the active substance of the first coating is 5 μm to 12 μm, and the D50 particle size of the active substance of the second coating is 1 μm to 7 μm.

[0008] According to the negative electrode sheet of the embodiment of the present invention, the first coating layer and the second coating layer are sequentially arranged outside the current collector, and the particle size of the active material in the first coating layer and the second coating layer is relatively small, which is conducive to improving the compaction density of the negative electrode sheet, improving the energy density of the battery, increasing the contact points between the active materials and the active materials, and between the active materials and the current collector, and improving the battery-level charge and discharge rate performance. At the same time, the particle size of the active material of the second coating layer is smaller than the particle size of the active material of the first coating layer, so that the side contacting the diaphragm is the second coating layer, which can effectively reduce the short circuit caused by the morphology hardness of the active material of the second coating layer, improve the process yield, and extend the service life of the battery.

[0009] According to some embodiments of the present invention, both the first coating layer and the second coating layer include a binder, and the binder includes at least one of polyacrylic acid, sodium polyacrylate, styrene-butadiene rubber, polyvinyl alcohol, and polyvinylidene fluoride.

[0010] According to some embodiments of the present invention, the first coating layer further includes a low swelling binder having a swelling rate of 5% to 10%, and / or the second coating layer further includes a high swelling binder having a swelling rate of 70% to 80%.

[0011] According to some embodiments of the present invention, in the first coating, the added amount of the low swelling binder accounts for 20% to 60% of the total amount of the binder, calculated by mass percentage, and / or, in the second coating, the added amount of the high swelling binder accounts for 40% to 85% of the total amount of the binder.

[0012] According to some embodiments of the present invention, the low swelling binder includes at least one of polymethyl acrylate, polyethyl acrylate, 2-methylpolymethyl acrylate and 2-methylpolyethyl acrylate; and / or, the high swelling binder includes at least one of hydrogenated nitrile rubber, butadiene, styrene, acrylic acid and acrylic acid derivatives.

[0013] According to some embodiments of the present invention, the acrylic acid derivative includes at least one of acrylic acid ester and acrylic acid salt, and the acrylic acid salt includes at least one of sodium acrylate and lithium acrylate.

[0014] According to some embodiments of the present invention, the active material includes at least one of hard carbon, soft carbon, natural graphite, artificial graphite, silicon carbon and silicon oxygen.

[0015] According to some embodiments of the present invention, at least the surface of the active material of the second coating layer is coated with a carbon coating layer.

[0016] According to some embodiments of the present invention, the first coating layer and / or the second coating layer further includes: a dispersant and a conductive agent.

[0017] According to some embodiments of the present invention, the dispersant includes at least one of sodium carboxymethyl cellulose, polyvinyl pyrrolidone and lithium carboxymethyl cellulose; and / or the conductive agent includes at least one of carbon black, carbon nanotubes and graphene.

[0018] According to the method for preparing a negative electrode sheet of an embodiment of the second aspect of the present invention, a first coating slurry and a second coating slurry are prepared, the first coating slurry is arranged on the surface of the current collector to form a first coating, the second coating slurry is arranged on the surface of the first coating to form a second coating, and the mixture is dried to obtain the negative electrode sheet.

[0019] According to some embodiments of the present invention, the preparation of the first coating slurry includes the following steps: mixing the active substance, the conductive agent, the binder and the dispersant to obtain a first layer of powder mixture, and adding a solvent to obtain the first coating slurry; and / or, the preparation of the second coating slurry includes the following steps: mixing the active substance, the conductive agent, the binder and the dispersant to obtain a second layer of powder mixture, and adding a solvent to obtain the second coating slurry.

[0020] According to some embodiments of the present invention, the input ratio of the active substance, the conductive agent, the binder and the dispersant in the first coating slurry is (95-98): (0.5-1.4): (3-5): (0.1-0.6) by mass ratio; and / or, the input ratio of the active substance, the conductive agent, the binder and the dispersant in the second coating slurry is (94-97): (0.7-1.7): (2-4): (0.5-1.5) by mass ratio; and / or, the solvent includes at least one of N-methylpyrrolidone and deionized water.

[0021] According to some embodiments of the present invention, the drying includes a drying process, the temperature of the drying process is 100° C. to 180° C., and the time of the drying process is 0.5 h to 1 h.

[0022] According to some embodiments of the present invention, the preparation of the second coating slurry includes the following steps: adding a surface modifier to the second layer powder mixture, wherein the surface modifier includes at least one of ethylene tar, coal tar, coal asphalt, rubber plasticizer, styrene-butadiene rubber, urea-formaldehyde resin, monosaccharide compounds and polysaccharide compounds.

[0023] According to a battery of an embodiment of the third aspect of the present invention, the battery comprises a positive electrode sheet, a separator and a negative electrode sheet, and the negative electrode sheet is the negative electrode sheet of the embodiment of the first aspect of the present invention or the negative electrode sheet prepared by the method for preparing the negative electrode sheet of the embodiment of the second aspect of the present invention.

[0024] The electrical equipment according to the fourth embodiment of the present invention comprises the battery according to the third embodiment of the present invention.

[0025] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 Schematic diagram of a negative electrode sheet according to an embodiment of the present invention.

[0027] Reference numerals: 100: negative electrode; 1: current collector; 2: first coating; 3: second coating. DETAILED DESCRIPTION

[0028] Reference below Figure 1 A negative electrode sheet 100 according to an embodiment of the present invention is described.

[0029] like Figure 1 As shown, the negative electrode sheet 100 according to an embodiment of the present invention includes a current collector 1 , a first coating layer 2 and a second coating layer 3 .

[0030] Specifically, the first coating 2 is disposed on the surface of the current collector 1. The second coating 3 is disposed on the side of the first coating 2 away from the current collector 1. The first coating 2 and the second coating 3 include active materials, the D50 particle size of the active materials of the first coating 2 is greater than the D50 particle size of the active materials of the second coating 3, the D50 particle size of the active materials of the first coating 2 is 5 μm to 12 μm, and the D50 particle size of the active materials of the second coating 3 is 1 μm to 7 μm.

[0031] For example, in Figure 1 In the example, the first coating 2 and the second coating 3 are sequentially provided on each side of the current collector 1. Compared with the conventional negative electrode sheet coating, the particle size of the active material of the first coating 2 and the second coating 3 is smaller, which is beneficial to improve the compaction density of the negative electrode sheet 100 and improve the battery energy density. At the same time, there are many contact points between the active materials and between the active materials and the current collector 1, which can effectively improve the rate performance of the battery.

[0032] At the same time, the particle size of the active material of the first coating 2 adjacent to the current collector 1 is larger, the porosity of the first coating 2 is larger, and the wetting effect is better, which can improve the rate performance of the battery. The particle size of the active material of the second coating 3 away from the current collector 1 is smaller, so that the side in contact with the diaphragm is the second coating 3, which can effectively reduce the short circuit caused by the morphology and hardness of the active material of the second coating 3, improve the process yield, and improve the battery-level charge and discharge rate performance.

[0033] The actual number of layers of the first coating 2 and the second coating 3 is not specifically limited here, that is, the first coating 2 and / or the second coating 3 can be one layer or more layers, wherein the first coating 2 is always arranged between the current collector 1 and the second coating 3, and the second coating 3 is located at the outermost side and is suitable for contacting with the diaphragm.

[0034] The current collector 1 includes at least one of copper, stainless steel, aluminum, nickel, titanium, calcined carbon and aluminum-cadmium alloy, which is not specifically limited here.

[0035] The particle size of the active material in the negative electrode sheet 100 can be detected by the following steps: 1) After the first coating 2 and / or the second coating 3 are scraped out for sampling, the first coating 2 and / or the second coating 3 are redissolved in a deionized water solvent; 2) using an ultrasonic cleaner to ultrasonicate the solution for at least 30 minutes and then using magnetic stirring for 1 hour to 3 hours to fully disperse the active substance in the first coating 2 and / or the second coating 3; 3) Wash with ethanol and deionized water alternately 2-3 times; 4) After filtering out the precipitate, the supernatant was placed in an oven at 100°C-180°C and baked for 0.5h-1h until the material was completely dried to form a test sample; 5) Use a laser particle size tester to test the particle size of the test sample.

[0036] The D50 of the particle size of the active substance of the first coating layer 2 and the D50 of the particle size of the active substance of the second coating layer 3 can be obtained through the number distribution percentage.

[0037] According to the negative electrode sheet 100 of the embodiment of the present invention, the first coating layer 2 and the second coating layer 3 are sequentially arranged outside the current collector 1. The particle size of the active material in the first coating layer 2 and the second coating layer 3 is relatively small, which is conducive to improving the compaction density of the negative electrode sheet 100, improving the battery energy density, increasing the contact points between the active materials and the active materials, and between the active materials and the current collector 1, and improving the battery level charge and discharge rate performance. At the same time, the particle size of the active material of the second coating layer 3 is smaller than the particle size of the active material of the first coating layer 2, so that the side contacting the diaphragm is the second coating layer 3, which can effectively reduce the short circuit caused by the morphology hardness of the active material of the second coating layer 3, improve the process yield, and extend the service life of the battery.

[0038] According to some embodiments of the present invention, referring to Figure 1 , the first coating layer 2 and the second coating layer 3 both include a binder. The binder can fully bond the solid components such as the active material together, increase the integrity of the first coating layer 2 and the second coating layer 3, increase the hardness, flexibility and wear resistance of the first coating layer 2 and the second coating layer 3, and at the same time facilitate the first coating layer 2 and the second coating layer 3 to be stably and firmly attached to the current collector 1.

[0039] The binder includes at least one of polyacrylic acid, sodium polyacrylate, styrene-butadiene rubber, polyvinyl alcohol and polyvinylidene fluoride. The above binders are all polymers with good dispersibility and good moldability. Therefore, using at least one of the above binders is conducive to improving the integrity and quality of the first coating 2 and the second coating 3, and is conducive to improving the quality of the negative electrode sheet 100.

[0040] Furthermore, the first coating 2 also includes a low swelling binder with a swelling rate of 5% to 10%, and / or the second coating 3 also includes a high swelling binder with a swelling rate of 70% to 80%. Therefore, the first coating 2 uses a low swelling binder with a swelling rate of 5% to 10%, and the second coating 3 uses a high swelling binder with a swelling rate of 70% to 80%, which can further improve the diffusion rate of ions such as sodium ions during the charge and discharge process, reduce the concentration polarization of the surface layer of the negative electrode sheet 100, reduce the resistivity of the negative electrode sheet 100, and significantly improve the rate and cycle performance of the battery.

[0041] Compared with single-layer coating, the use of the first coating 2 and the second coating 3 above optimizes the migration path of ions and / or electrons between active materials and between active materials and electrolyte during battery cycling by layering large and small particles and matching high swelling binders and low swelling binders, thereby improving the charge and discharge rate performance of the battery.

[0042] When the low swelling binder contacts water or other polar solvents, it will not significantly absorb these substances, thereby avoiding volume expansion caused by water absorption. The low swelling binder can maintain its dimensional stability under different environmental conditions and has good durability. At the same time, the low swelling binder has high mechanical strength and is not easy to deform. Therefore, the use of the low swelling binder is conducive to improving the consistency and stability of the first coating 2.

[0043] When the high swelling binder contacts with solvents or other liquids, it can significantly absorb these liquids and cause its own volume to expand. The use of the high swelling binder in the second coating 3 is conducive to improving the expansion of the second coating 3. When the second coating 3 contacts with the electrolyte, it is easy to expand. The porosity of the expanded second coating 3 increases, so that the negative electrode sheet 100 is more fully infiltrated, which is conducive to optimizing the rate performance of the battery.

[0044] The swelling rate of the binder can be tested by the following steps: 1) Immerse the stage into a container filled with electrolyte and record the height h0 of the electrolyte level when the stage is empty; 2) Place the adhesive film on the stage and immerse it in the same container to the same depth and record the electrolyte level h1; 3) Immerse the adhesive film in the electrolyte to make it swell, and let it stand for 12h-24h to ensure complete swelling. During the immersion process, ensure that the adhesive film is always completely below the electrolyte level; 4) After the adhesive film is completely swollen, adjust the stage immersion depth to the same depth as before swelling and record the liquid level h2; 5) Lift the stage from the electrolyte, remove it after the electrolyte on the adhesive film surface is drained, immerse the empty stage into the electrolyte to the same depth, and record the liquid level h3; 6) Calculate the swelling ratio of the binder = (h3-h2) / (h1-h0).

[0045] Furthermore, in the first coating 2, the amount of low swelling binder added is 20% to 60% of the total amount of binder by mass percentage. The amount of low swelling binder added is a reasonable proportion of the total amount of binder, which is conducive to giving full play to the role of low swelling binder, thereby facilitating the increase of the setting stability of the first coating 2, so that the first coating 2 can be reliably arranged outside the current collector 1, and increasing the reliability and stability of the connection between the first coating 2 and the second coating 3.

[0046] In terms of mass percentage, the amount of the high swelling binder added in the second coating layer 3 accounts for 40% to 85% of the total amount of the binder. The amount of the high swelling binder added is relatively reasonable, which is conducive to giving full play to the role of the high swelling binder in the second coating layer 3, making the expanded porosity of the second coating layer 3 relatively reasonable, so that the electrolyte can infiltrate the negative electrode sheet 100, which is conducive to optimizing the rate performance of the battery.

[0047] According to some embodiments of the present invention, the low swelling binder includes at least one of polymethyl acrylate, polyethyl acrylate, 2-methyl polymethyl acrylate and 2-methyl polyethyl acrylate. The above low swelling binders all have good mechanical strength and rigidity, and also show certain flexibility and impact resistance. At the same time, they also have good chemical stability. The use of the above low swelling binder effectively improves the setting stability and reliability of the first coating 2, thereby ensuring the reliability of the first coating 2 connecting the current collector 1 and the second coating 3, and improving the quality of the negative electrode sheet 100.

[0048] The high swelling binder includes at least one of hydrogenated nitrile rubber, butadiene, styrene, acrylic acid and acrylic acid derivatives. Hydrogenated nitrile rubber has good heat resistance, tensile strength and wear resistance; butadiene is a conjugated diene, which can be copolymerized with other monomers to achieve bonding; acrylic acid and its derivatives have excellent bonding strength, weather resistance and good adhesion to various surfaces. Therefore, using at least one of hydrogenated nitrile rubber, butadiene, styrene, acrylic acid and acrylic acid derivatives as a high swelling binder is conducive to improving the structural strength of the second coating 3. At the same time, by adjusting the ratio of different monomers, the hardness, elasticity and viscosity of the final product can be controlled, thereby meeting the use requirements of the high swelling binder.

[0049] Further, the acrylic acid derivative includes at least one of acrylic acid ester and acrylic acid salt. Acrylic acid derivatives have good adhesion, flexibility, transparency and weather resistance. Acrylic acid ester and acrylic acid salt are suitable for meeting the use requirements of high swelling adhesives through modification or copolymerization with other monomers.

[0050] Furthermore, the acrylate includes at least one of sodium acrylate and lithium acrylate. Sodium acrylate and lithium acrylate are both salt forms of acrylic acid, which can be obtained by reacting acrylic acid with a corresponding alkali metal (sodium or lithium). Sodium acrylate or lithium acrylate is used as a binder through polymerization, and has good water absorption. For example, the water absorption capacity of sodium polyacrylate makes it suitable for the moisture absorption needs of the negative electrode sheet. At the same time, it has good electrochemical stability and shows good stability in electrochemical applications. At least one of sodium acrylate and lithium acrylate is used as an acrylate, and a copolymer can be formed by modification or copolymerization with other monomers to improve the mechanical properties and chemical stability of the second coating 3.

[0051] In addition, the active material includes at least one of hard carbon, soft carbon, natural graphite, artificial graphite, silicon carbon and silicon oxygen. The above active materials have high theoretical capacity, good conductivity and low cost. At least one of the above active materials is used. During the charging and discharging process, ions can be embedded and de-embedded in the lattice of the active material, thereby realizing energy storage and release. The above active materials are relatively stable, which is conducive to maintaining the relative stability of the structure of the first coating 2 and the second coating 3 during the ion embedding and de-embedding process to ensure the cycle life electrical properties of the battery.

[0052] Furthermore, at least the active material surface of the second coating 3 is coated with a carbon coating layer. That is to say, only the active material surface of the second coating 3 may be coated with a carbon coating layer; or, the active material surfaces of the first coating 2 and the second coating 3 are coated with a carbon coating layer. For example, the carbon coating layer is provided on the active material surface of the second coating 3, which is conducive to coating the irregular and sharp positions on the surface of the active material, and avoiding the irregular and sharp positions on the surface of the active material piercing the diaphragm during the process, causing short circuits and other defects. At the same time, the carbon coating layer can effectively improve the conductivity of the second coating 3, reduce the surface resistance, and improve the rate performance of the battery.

[0053] According to some embodiments of the present invention, the first coating 2 and / or the second coating 3 further include: a dispersant and a conductive agent. A dispersant is a surfactant having two opposite properties, lipophilicity and hydrophilicity, in a molecule, which can reduce the tendency of solid or liquid particles to aggregate in a dispersed system and improve the uniform stability of a dispersion or suspension. The conductive agent forms a conductive network between active substances or between active substances and the current collector 1. The conductive agent can reduce the contact resistance of the negative electrode sheet 100, accelerate the movement rate of electrons, and increase the migration rate of ions, thereby improving the charge and discharge efficiency and service life of the battery.

[0054] Furthermore, the dispersant includes at least one of sodium carboxymethyl cellulose (CMC), polyvinylpyrrolidone (PVP) and lithium carboxymethyl cellulose (Li-CMC). Among them, CMC and PVP are both water-soluble synthetic polymers with good dispersibility and adhesion, which can effectively disperse the active material, prevent the active material from agglomerating, and improve the quality of the first coating 2 and the second coating 3. CMC enhances the physical strength of the electrode by forming a continuous network structure, which helps to maintain the structural integrity of the electrode material during the charge and discharge process, thereby improving the cycle performance of the battery. At the same time, it is beneficial to improve the fluidity and stability of the slurry of the first coating 2 and the second coating 3, making the slurry easy to apply and not easy to delaminate. Li-CMC can provide better electrochemical stability, dispersibility and adhesion strength. Due to its lithium salt form, Li-CMC is more stable in the electrolyte.

[0055] The conductive agent includes at least one of carbon black, carbon nanotubes and graphene. The above conductive agents all have a high specific surface area and good conductivity and are easy to disperse. Using at least one of the above conductive agents is conducive to improving the conductivity and toughness of the first coating 2 and the second coating 3.

[0056] According to the method for preparing the negative electrode sheet 100 of the second embodiment of the present invention, a first coating slurry and a second coating slurry are prepared, wherein the D50 particle size of the active material in the first coating slurry is 5 μm to 12 μm, the D50 particle size of the active material in the second coating slurry is 1 μm to 7 μm, and the D50 particle size of the active material in the first coating slurry is greater than the D50 particle size of the active material in the second coating slurry.

[0057] The first coating slurry is disposed on the surface of the current collector 1 to form a first coating 2, and the second coating slurry is disposed on the surface of the first coating 2 to form a second coating 3, and the mixture is dried to obtain a negative electrode sheet.

[0058] For example, the first coating slurry and the second coating slurry can be poured into a double-layer coating machine to coat the first coating slurry and the second coating slurry on the current collector 1 to obtain a coated electrode sheet, and the coated electrode sheet is dried in an oven and then rolled and cut to obtain a double-layer coated finished negative electrode sheet 100.

[0059] The method for preparing the negative electrode sheet 100 according to the embodiment of the present invention is conducive to ensuring the reliability of coating the first coating 2 and the second coating 3 on the current collector 1, improving the quality of the negative electrode sheet 100, and the preparation method is relatively simple, which is conducive to improving the preparation efficiency of the negative electrode sheet 100 and reducing the cost of the negative electrode sheet 100.

[0060] Furthermore, preparing the first coating slurry includes the following steps: mixing the active substance, the conductive agent, the binder and the dispersant to obtain a first layer of powder mixture, and adding a solvent to obtain the first coating slurry; and / or, preparing the second coating slurry includes the following steps: mixing the active substance, the conductive agent, the binder and the dispersant to obtain a second layer of powder mixture, and adding a solvent to obtain the second coating slurry.

[0061] Among them, the solvent is conducive to the dissolution and dispersion of the active material, dispersant and conductive agent, etc., and is conducive to improving the quality uniformity of the first coating 2 or the second coating 3, so as to facilitate the first coating 2 and the second coating 3 to fully play their roles. The preparation methods of the first coating slurry and the second coating slurry are similar, and the corresponding active material, conductive agent, binder and dispersant are mixed and then added to the solvent to obtain. The above preparation method is relatively simple, which is conducive to improving the preparation efficiency of the negative electrode sheet 100 and reducing the cost of the negative electrode sheet 100.

[0062] The active substance may be added all at once or in batches, without specific limitation.

[0063] Furthermore, in terms of mass ratio, the input ratio of active material, conductive agent, binder and dispersant in the first coating slurry is (95-98): (0.5-1.4): (3-5): (0.1-0.6). The input ratio of active material, conductive agent, binder and dispersant in the first coating slurry is relatively reasonable, and the active material, conductive agent and binder can be fully dispersed in the dispersant, so that the prepared first coating slurry is relatively uniform, which is conducive to the coating of the first coating slurry on the current collector 1, so that the formed first coating 2 has better adhesion on the current collector 1, thereby increasing the setting stability and surface strength of the first coating 2 and the current collector 1.

[0064] In terms of mass ratio, the input ratio of active material, conductive agent, binder and dispersant in the second coating slurry is (94-97): (0.7-1.7): (2-4): (0.5-1.5). The input ratio of active material, conductive agent, binder and dispersant in the second coating slurry is relatively reasonable, so that the active material, conductive agent and binder are dispersed more evenly in the dispersant, which improves the uniformity of the second coating 3 formed after coating, and at the same time enables the second coating 3 to be stably attached to the outside of the first coating 2, thereby improving the integrity and durability of the negative electrode sheet 100.

[0065] The solvent includes at least one of N-methylpyrrolidone (NMP) and deionized water. Among them, N-methylpyrrolidone is a highly polar non-protonic polar solvent with good solubility and high stability, so the use of N-methylpyrrolidone is conducive to improving the adhesion, stability and reliability of the first coating 2 and the second coating 3. Deionized water is water treated by ion exchange resin and contains almost no minerals or ionic impurities, which can avoid the influence of impurities in the solvent on the first coating 2 or the second coating 3.

[0066] In addition, drying includes a drying treatment, the temperature of the drying treatment is 100°C to 180°C, and the time of the drying treatment is 0.5h to 1h. The drying treatment can shorten the time required for drying and improve the efficiency of production or processing. At the same time, by adjusting parameters such as temperature and humidity, the drying process can be accurately controlled to ensure the quality consistency and stability of the final product. The temperature and time of the above-mentioned drying treatment are relatively reasonable, which is conducive to the full drying of the first coating slurry and the second coating slurry to form the first coating 2 and the second coating 3, and can avoid wasting energy.

[0067] According to some embodiments of the present invention, preparing the second coating slurry includes the following steps: adding a surface modifier to the second layer powder mixture to form a carbon coating on the surface of the active substance, wherein the surface modifier includes at least one of ethylene tar, coal tar, coal asphalt, rubber plasticizer, styrene-butadiene rubber, urea-formaldehyde resin, monosaccharide compounds and polysaccharide compounds. In other words, the raw material of the carbon coating is a surface modifier. Carbonization of the surface modifier to form a carbon coating refers to the process of introducing a carbon-based coating on the surface of the active substance by chemical or physical means to form an amorphous carbon coating. The above-mentioned surface modifier has the advantages of improving surface properties, such as wettability, adhesion, wear resistance, etc., and is also beneficial to enhancing the conductivity, corrosion resistance or biocompatibility of the carbon coating.

[0068] According to a battery (not shown) according to an embodiment of the third aspect of the present invention, the battery includes a positive electrode sheet, a separator and a negative electrode sheet 100, and the negative electrode sheet 100 is the negative electrode sheet 100 according to the embodiment of the first aspect of the present invention or the negative electrode sheet 100 prepared by the preparation method of the negative electrode sheet 100 according to the embodiment of the second aspect of the present invention.

[0069] According to the battery of the embodiment of the present invention, by using the above-mentioned negative electrode sheet 100, damage to the separator is avoided, the reliability of the battery is improved, and at the same time, it is beneficial to improve the rate performance of the battery, thereby improving the market competitiveness of the battery.

[0070] An electrical device (not shown) according to an embodiment of a fourth aspect of the present invention comprises a battery according to an embodiment of the third aspect of the present invention.

[0071] The electric device according to the embodiment of the present invention, by adopting the above-mentioned battery, is conducive to increasing the functional stability and reliability of the electric device, thereby improving the user experience of the power supply device.

[0072] Other structures and operations of the battery and the electrical device according to the embodiments of the present invention are known to those skilled in the art and will not be described in detail here.

[0073] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention. In addition, if not explicitly stated, all reagents used in the following embodiments are commercially available, or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.

[0074] The specific data of the particle size (μm) of the active material of the first coating 2 and the particle size (μm) of the active material of the second coating 3 of the embodiment and the comparative example are shown in Table 1. The first coating 2 and the second coating 3 of the embodiment both use hard carbon as the active material, deionized water as the solvent, and the binder includes styrene-butadiene rubber.

[0075] Example Step 1: Prepare the first coating slurry Calculated by mass ratio, the hard carbon: conductive agent: binder: dispersant in the first coating slurry is 95.2:1.3:3:0.5, wherein the solid content of the first coating slurry is 60%.

[0076] 1) Using deionized water as solvent, add dispersant sodium carboxymethyl cellulose and disperse evenly to form a transparent glue solution; 2) Add conductive agent carbon black and disperse evenly at high speed; 3) Add hard carbon active material in batches and stir to mix evenly; 4) adding low swelling binder polymethyl acrylate and conventional binder styrene-butadiene rubber in a mass ratio of 2:8, mixing evenly, and adjusting the slurry viscosity to about 5000 Pa·s to obtain a first coating slurry.

[0077] Step 2: Prepare the second coating slurry Calculated by mass ratio, the hard carbon: conductive agent: binder: dispersant in the second coating slurry is 94.5:1.5:3.4:0.6, and the solid content of the second coating slurry is 58%.

[0078] 1) Using deionized water as solvent, add dispersant sodium carboxymethyl cellulose and disperse evenly to form a transparent glue solution; 2) Add conductive agent carbon black and disperse evenly at high speed; 3) Add hard carbon active material in batches and stir to mix evenly; 4) High swelling binder hydrogenated nitrile rubber and conventional binder styrene butadiene rubber were added in a mass ratio of 6:4, mixed evenly, and the slurry viscosity was adjusted to about 5000 Pa·s to obtain a second coating slurry.

[0079] Step 3: Prepare the negative electrode sheet 100 1) The first coating slurry is evenly coated on the negative electrode current collector 1. The density of the first coating 2 is 200g / m 2 In this embodiment, the first coating slurry is directly coated on the surface of the current collector 1, but the scope of application of this patent includes but is not limited to other current collectors 1 with surface pretreatment such as conductive coatings; 2) The second coating slurry is evenly applied to the side of the first coating 2 away from the current collector 1. The density of the second coating 3 is 200 g / m 2 The total density of the first coating 2 and the second coating 3 is 400 g / m 2 After rolling, die cutting and baking, the negative electrode sheet 100 is obtained.

[0080] Step 4: Prepare the positive electrode Calculated by mass ratio, the ratio of sodium ferric pyrophosphate (NFPP): conductive agent: binder in the positive electrode coating slurry is 94.5:1.5:4, and the solid content in the positive electrode coating slurry is 60%.

[0081] 1) Use N-methylpyrrolidone (NMP) as solvent, add binder (polyvinylidene fluoride, PVDF) and disperse evenly to form a transparent glue solution; 2) Add conductive agent (one or more conductive agents such as carbon black, carbon nanotubes, graphene, etc.) and disperse evenly at high speed; 3) Add NFPP material in batches, stir and mix evenly to obtain positive electrode coating slurry.

[0082] 4) Apply the positive electrode coating slurry on the positive electrode current collector 1, and the coating surface density is 400g / m 2 , and then the positive electrode sheet is obtained after rolling, die cutting and baking.

[0083] The electrolyte uses NaPF6 with a concentration of 1.1 mol / L as the solute, and uses a mixed solvent with a mass ratio of ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 3.0:5.0:3.25. The negative electrode sheet 100 and the positive electrode sheet prepared in step 3 and step 4 are assembled with a separator (made of polypropylene), and the above electrolyte is injected to obtain a negative electrode double-layer coated sodium ion battery.

[0084] The preparation steps of the comparative example are substantially the same as those of the embodiment.

[0085] Table 1 is the data of the embodiments and comparative examples of the present disclosure

[0086] Performance Testing The sodium ion battery prepared above was subjected to performance tests, and the test items included 25°C 1C rate 500cyc cycle capacity retention rate, 3C capacity retention rate, pole piece limit compaction, pole core short circuit rate, and the test method was as follows: 1) 25℃ cycle capacity test: Charge to 3.6V at 1 / 3C constant current at 25℃, let stand for 30 minutes, then discharge to 2.0V at 1C constant current, cycle 500 times, and compare capacity retention rate.

[0087] 2) 3C rate discharge test: Charge to 3.6V at 1 / 3C constant current at 25℃, let stand for 30 minutes, then discharge to 2.0V at 3C constant current, and compare the discharge capacity ratio at different rates.

[0088] 3) Pole piece limit compaction test: Place the sample pole piece on a roller press and gradually increase the pressure for continuous rolling. After rolling, measure the pole piece thickness under different pressures, calculate the compaction and observe the pole piece status.

[0089] 4) Pole core short circuit rate test: After applying 5kg pressure on the surface of the sample pole core, use an insulation pulse tester to test the pole core with a test voltage of 200V and a test time of 250ms.

[0090] Table 2 is the test data of the embodiments and comparative examples of the present disclosure.

[0091] Test results analysis Comparing Example 1 with Comparative Examples 1 and 2, by adjusting the particle size of the active material of the second coating 3, as the active material increases, the pole piece limit compaction will also increase accordingly, but too large a compaction density will lead to a decrease in the porosity of the negative electrode sheet 100, affecting the cycle and rate performance. The increase in the active material of the second coating 3 will also increase the risk of short circuit caused by puncturing the diaphragm, so it is considered that the appropriate D50 particle size of the active material of the second coating 3 is 1μm-7μm.

[0092] Comparing Example 1 with Comparative Examples 3 and 4, by adjusting the particle size of the active material of the first coating 2, as the active material increases, the pole piece limit compaction will also increase accordingly. However, too large a compaction density will lead to a decrease in the pole piece porosity, affecting the cycle and rate performance, so it is considered that the appropriate D50 particle size of the active material of the first coating 2 is 5μm-12μm.

[0093] By comparing Examples 1-13 and Comparative Example 5, it can be found that when the D50 particle size of the active material of the first coating 2 is larger than the D50 particle size of the active material of the second coating 3, the cycle and rate performance of the battery are better, and when the D50 particle size of the active material of the first coating 2 is smaller than the D50 particle size of the active material of the second coating 3, the cycle and rate performance of the battery are poor. Therefore, it is believed that the D50 particle size of the active material of the first coating 2 is larger than the D50 particle size of the active material of the second coating 3, which is beneficial to improving the cycle and rate performance of the battery.

[0094] Comparing Examples 1, 6, 7, 10 and 11, by adjusting the swelling rate of the binder of the first coating 2, as the swelling rate of the binder increases, the porosity of the negative electrode sheet 100 increases after liquid absorption and activation, which can slightly improve the rate performance. However, excessive porosity will lead to a decrease in the ultimate compaction of the negative electrode sheet 100, and the increase in the specific surface area of ​​the negative electrode sheet 100 will affect the cycle performance, so it is considered that the appropriate swelling rate of the binder of the first coating 2 is 5%-10%.

[0095] Comparing Examples 1, 8, 9, 12 and 13, by adjusting the swelling rate of the binder of the second coating 3, as the swelling rate of the binder increases, the porosity of the negative electrode sheet 100 increases after liquid absorption and activation, which can improve the rate performance. However, excessive porosity will lead to a decrease in the ultimate compaction of the negative electrode sheet 100, and the increase in the specific surface area of ​​the negative electrode sheet 100 will affect the cycle performance, so it is considered that the appropriate swelling rate of the binder of the second coating 3 is 70%-80%.

[0096] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.

[0097] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A negative electrode sheet, characterized in that: include: current collector; a first coating layer, the first coating layer being disposed on the surface of the current collector; a second coating layer, the second coating layer being disposed on a side of the first coating layer away from the current collector, The first coating and the second coating include active substances, the D50 particle size of the active substances in the first coating is larger than the D50 particle size of the active substances in the second coating, the D50 particle size of the active substances in the first coating is 5 μm to 12 μm, and the D50 particle size of the active substances in the second coating is 1 μm to 7 μm.

2. The negative electrode sheet according to claim 1, characterized in that: The first coating layer and the second coating layer both include a binder, and the binder includes at least one of polyacrylic acid, sodium polyacrylate, styrene-butadiene rubber, polyvinyl alcohol, and polyvinylidene fluoride.

3. The negative electrode sheet according to claim 2, characterized in that: The first coating layer further includes a low swelling binder having a swelling rate of 5% to 10%, and / or the second coating layer further includes a high swelling binder having a swelling rate of 70% to 80%.

4. The negative electrode sheet according to claim 3, characterized in that: In the first coating, the amount of the low swelling binder added is 20% to 60% of the total amount of the binder, and / or, in the second coating, the amount of the high swelling binder added is 40% to 85% of the total amount of the binder, calculated by mass percentage.

5. The negative electrode sheet according to claim 3 or 4, characterized in that: The low swelling binder comprises at least one of polymethyl acrylate, polyethyl acrylate, 2-methylpolymethyl acrylate and 2-methylpolyethyl acrylate; and / or the high swelling binder comprises at least one of hydrogenated nitrile rubber, butadiene, styrene, acrylic acid and acrylic acid derivatives.

6. The negative electrode sheet according to claim 5, characterized in that: The acrylic acid derivative includes at least one of acrylic acid ester and acrylic acid salt, and the acrylic acid salt includes at least one of sodium acrylate and lithium acrylate.

7. The negative electrode sheet according to claim 1, characterized in that: The active material includes at least one of hard carbon, soft carbon, natural graphite, artificial graphite, silicon carbon and silicon oxygen.

8. The negative electrode sheet according to claim 7, characterized in that: At least the surface of the active material of the second coating layer is coated with a carbon coating layer.

9. The negative electrode sheet according to any one of claims 1 to 8, characterized in that: The first coating layer and / or the second coating layer further includes: a dispersant and a conductive agent.

10. The negative electrode sheet according to claim 9, characterized in that: The dispersant comprises at least one of sodium carboxymethyl cellulose, polyvinyl pyrrolidone and lithium carboxymethyl cellulose; and / or, The conductive agent includes at least one of carbon black, carbon nanotubes and graphene.

11. A method for preparing a negative electrode sheet according to any one of claims 1 to 10, characterized in that: preparing a first coating slurry and a second coating slurry, The first coating slurry is disposed on the surface of the current collector to form a first coating, and the second coating slurry is disposed on the surface of the first coating to form a second coating, and the coating is dried to obtain the negative electrode sheet.

12. The preparation method according to claim 11, characterized in that: The preparation of the first coating slurry comprises the following steps: mixing the active material, the conductive agent, the binder and the dispersant to obtain a first layer of powder mixture, and adding a solvent to obtain the first coating slurry; And / or, the preparation of the second coating slurry comprises the following steps: mixing the active material, the conductive agent, the binder and the dispersant to obtain a second layer of powder mixture, and adding a solvent to obtain the second coating slurry.

13. The preparation method according to claim 12, characterized in that: In terms of mass ratio, the input ratio of the active material, the conductive agent, the binder and the dispersant in the first coating slurry is (95-98): (0.5-1.4): (3-5): (0.1-0.6); And / or, in terms of mass ratio, the input ratio of the active material, the conductive agent, the binder and the dispersant in the second coating slurry is: (94-97): (0.7-1.7): (2-4): (0.5-1.5); And / or, the solvent includes at least one of N-methylpyrrolidone and deionized water.

14. The preparation method according to claim 11, characterized in that: The drying includes a drying process, the temperature of the drying process is 100° C. to 180° C., and the time of the drying process is 0.5 h to 1 h.

15. The preparation method according to claim 12, characterized in that: The preparation of the second coating slurry includes the following steps: adding a surface modifier to the second layer powder mixture, wherein the surface modifier includes at least one of ethylene tar, coal tar, coal asphalt, rubber plasticizer, styrene-butadiene rubber, urea-formaldehyde resin, monosaccharide compounds and polysaccharide compounds.

16. A battery, characterized in that: The battery comprises a positive electrode sheet, a separator and a negative electrode sheet, wherein the negative electrode sheet is the negative electrode sheet according to any one of claims 1 to 10 or a negative electrode sheet prepared by the method for preparing a negative electrode sheet according to any one of claims 11 to 15.

17. An electrical equipment, characterized in that: Comprising the battery of claim 16.

Citation Information

Patent Citations

  • Negative plate and lithium ion battery comprising same

    CN111916667A

  • Silicon-containing negative plate and lithium ion battery comprising same

    CN112467079A

  • Negative plate and battery

    CN113097427A

  • Pole piece, secondary battery and electric device comprising same

    CN115939307A

  • Negative plate, lithium ion battery and preparation method

    CN116682939A

Cited By

  • Electrode assembly and lithium ion battery

    CN117525276A

  • Preparation method of sodium-ion battery negative electrode plate with composite coating and application of sodium-ion battery negative electrode plate

    CN120767293A

  • Pole piece and electrochemical device

    CN121355179A